Comportamento morfofisiológico de mudas de café conilon propagadas por estaquia e enxertia - Andrade Júnior, Saul de (2012)
Its objective is to evaluate the seedlings growth disseminated by grafting and cutting and to characterize gas exchanges and chlorophyll fluorescence a in conilon coffee. The experiment was conducted at the seedling production vivarium of Incaper‟s Experimental Farm in Marilândia city in Espírito Santo. In the grafting, seedlings from seminiferous propagation of Coffea canephora species, „Robusta Tropical 8151‟ were used as rootstocks, and as graft, six clones Conilon „Vitória Incaper 8142‟. The cutting was done with six clones used in the grafting. The experimental design was in randomized blocks with twelve treatments and five repetitions composed by twelve seedlings. After 130 days the grafting read the variables of gas exchanges and chlorophyll fluorescence a after 150 days means of variables were evaluated and they were compared by Scheffé test with a probability of 5%. The grafted seedlings were superior in all growth characteristics. Significant differences weren‟t detected to gas exchanges in none of the cutting and grafting contrasts and the same hasn‟t occurred to chlorophyll fluorescence a parameters and when the study considered the maturation stage the materials showed no differences among them.